GMO – Vrsta užasa ili odgovor na glad u svetu!? - Donev, Dejan (Bioetičko društvo u BiH, 2015)
Humanity is changing with unprecedented speed and the society for the first time is trying to control so far the unknown transformation of living beings. It is so because the man already produces not only bacteria, viruses and plants, but also hybrid and even "cross" animals that inherited transferable traits which origin from the genetic interior of different species. The last reflects the radical difference between genetic manipulation and hybridization that so far reflected the development of agriculture. Even more, man today makes a change which by its meaning is unique – the insertation of human gene, the gene of dog or germ in the corn becomes a reality. That’s why, since the beginning of 2004 started a heated debate - whether these organisms are kind of horror or response to the hunger that grows with the world population. The stakes are diverse: economic, environmental, health, political, scientific, legal ... but most of all ethical, because this issue fundamentally changes our understanding of life. It gives us the right to say that there are important issues that are no good to be avoided, or overly simplified, i.e. because of the attempt once again to reevaluate the conception of life, a man can open a Pandora's box!
GMO - a kind of horror or an answer to world hunger!?
Keywords: GMO, bioethics, health, human gene